The chronotope of the road in the novel of Antonio Tabucchi «It’s getting later all the time» - Tur, Valiantsina I. (Journal of the Belarusian State University. Philology, 2019)
The article focuses on such important element of the narrating world as the chronotope. In particular, its significance in the texts of contemporary fiction is emphasized. It is also fundamental for understanding of the postmodern reality that assumes a spatial focus. The specifications of the chronotope of the road in the novel «It’s getting later all the time» of the Italian writer Antonio Tabucchi are analyzed. The chronotope of the road in this literary work helps to reveal the particulars of the characters’ internal world, of their relationship with the other and with the objective reality. The characters move in the time of their memory and this movement represents the attempt to rethink the past and to find the unrealized future. The writer concentrates on the subjective time perception, on the indivisibility of the past, the present and the future as well as on the space of the subjective experience. As the result, the described places become symbolic. They are related not so much to the external world as to the character’s imagination and memory. During such mental travelling the characters of the novel realize that their movement is only an illusion and they can never get the lost.